2009
DOI: 10.1080/09603120802712750
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with clinic visits during the 1999 forest fires near the Hoopa Valley Indian Reservation, California, USA

Abstract: Forest fires burned near the Hoopa Valley Indian Reservation in northern California from late August until early November in 1999. The fires generated particulate matter reaching hazardous levels. We assessed the relationship between patients seeking care for six health conditions and PM(10) exposure levels during the 1999 fires and during the corresponding period in 1998 when there were no fires. Multivariate logistic regression analysis indicated that daily PM(10) levels in 1999 were significant predictors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 8 publications
2
45
0
Order By: Relevance
“…Our study, similar to many wildfire epidemiological studies, did not find evidence of significant effects of PM 2.5 from wildfires on hospitalizations or ED visits for cardiovascular disease (Hanigan et al, 2008;Henderson et al, 2011;Martin et al, 2013;Morgan et al, 2010). A few recent papers, however, have found significant effects for out-of-hospital cardiac arrests (Dennekamp et al, 2015;Haikerwal et al, 2015), hospitalizations for hypertension (Arbex et al, 2010), cardiovascular clinic visits (Lee et al, 2009), ED visits for congestive heart failure (Rappold et al, 2011), and hospitalizations for IHD (Johnston et al, 2007).…”
Section: Discussionsupporting
confidence: 84%
“…Our study, similar to many wildfire epidemiological studies, did not find evidence of significant effects of PM 2.5 from wildfires on hospitalizations or ED visits for cardiovascular disease (Hanigan et al, 2008;Henderson et al, 2011;Martin et al, 2013;Morgan et al, 2010). A few recent papers, however, have found significant effects for out-of-hospital cardiac arrests (Dennekamp et al, 2015;Haikerwal et al, 2015), hospitalizations for hypertension (Arbex et al, 2010), cardiovascular clinic visits (Lee et al, 2009), ED visits for congestive heart failure (Rappold et al, 2011), and hospitalizations for IHD (Johnston et al, 2007).…”
Section: Discussionsupporting
confidence: 84%
“…Study findings varied geographically, with no report of a statistically significant cardiovascular impact of wildfire smoke in any study from Australia and Canada (seven out of 14) (Crabbe 2012; Hanigan et al , 2008; Henderson et al , 2011; Johnston et al , 2007; Martin et al , 2013; Moore et al , 2006; Morgan et al , 2010). Contrastingly, five out of six U.S. studies reported that exposure to wildfire smoke was associated with hospital admissions for cardiovascular diseases, such as cardiac arrests, or symptoms such as chest pain (Delfino et al , 2009; Lee et al , 2009; Rappold et al , 2012; Rappold et al , 2011). All studies assessed cardiovascular disease by hospital admissions or emergency room visits.…”
Section: Resultsmentioning
confidence: 91%
“…Associations for longer lags (greater than five days) between exposure and hospitalization were not directly investigated in any study. From cross-sectional studies there were increases in primary care contacts for a 12-week period of exposure to wildfire smoke in California (Lee et al , 2009) and a five-week exposure period in Canada (Moore et al , 2006) compared to the same period in previous years when there were no fires. However, it remains unclear as to whether admissions increased due to high acute exposures over short periods (days) and/or lower levels accumulated over a longer period (months).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No association was found with wildfire smoke and ischemic heart disease hospitalizations in California, while another study found an increase in clinic‐based ischemic heart disease visits among Native Americans of the Hoopa tribe of northern California 43, 44. An Australian study mentioned earlier found increased rates of hospital admissions and ED visits for ischemic heart disease among women and adults aged >65 years at lag day 2 15…”
Section: Discussionmentioning
confidence: 94%